Kualitas Audit: Karakteristik Auditor dan Time Budget Pressure - Salama Benty Dibyani; Indira Januarti (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2025)
Main Purpose - This research aims to examine the influence of professional skepticism, moral reasoning, religiosity, and time budget pressure on audit quality. Method - This study uses a quantitative method with the sampling technique determined through census sampling. The analytical tool used is regression, processed with SmartPLS version 4. Main Findings - The phenomenon of the increasing number of fraud cases is supported by the high volume of corruption complaints from the public, with the DKI Jakarta Province ranking first for the most complaints and becoming one of the regions with the largest amount of regional financial recovery. The research results show that Professional Skepticism and Religiosity have a positive effect on audit quality. Meanwhile, Moral Reasoning has no positive effect on audit quality and Time Budget Pressure has no negative effect on audit quality.Theory and Practical Implications - The implications of the results of this research show that auditors who have religiosity and professional skepticism can produce good audit quality, because it needs to be maintained and if possible, always improve it. This research provides an important contribution to expanding existing theory in the fields of auditing, ethics, and decision making in improving audit quality. The novelty of this research is in the religiosity variable and the object of research is the government auditor (BPKP).Novelty - The novelty of this research lies in the research object and the independent variables (moral reasoning, religiosity, and time budget pressure).